(untitled) (Nexo Revista Científica, 2023)
The article is devoted to the formation of approaches to the multi-vector development of tourism enterprises. The multi-vector development of tourism enterprises is one of the most complex systems that consider all key areas and types of activities, divisions, and spheres of functioning. The purpose of the work is to substantiate approaches to assessing the effectiveness of functioning and the main directions of strategic development of tourism enterprises at various levels. The authors identify organizational transformation models, risks of multi-vector development, features of the strategy, and communication of interaction with consumers of tourism services using qualitative methods of data analysis. The scenario approach to the development of enterprises within the framework of multi-vector development is a priority and can be implemented based on the introduction of innovative products by a tourism enterprise and provides for the renewal of technical and technological support, training, or recruitment of new personnel, the formation of a marketing policy for bringing tourism services to the market, informing consumers, creating or reorganizing service services. The authors establish that the proposed approaches to ensuring the multi-vector development of tourism enterprises allow for forming the basis for planning, organizing, controlling, regulating, and implementing high-quality multi-vector development of a company’s activities.